Social distancing mediates clinical work and depression: impact of the COVID-19 pandemic on nurses - Chen, Shu-Chen; Lee, Tony Szu-Hsien; Chao, En (Frontiers in Public Health, 2024)
BackgroundThe psychological well-being of nurses, during the COVID-19 pandemic has become a critical area of concern. This study examines the psychological impact of the pandemic on nurses, focusing on the mediating role of perceived social distance between work units and depression.MethodsThis study employed a cross-sectional design with respondent driven sampling. Anonymous questionnaire consisting of demographics, perceived social distancing and depression were distributed through email, Facebook, LINE, and other online platforms by key informants of nurses. A total of 1,064 volunteered questionnaires were collected, consisting of 1,032 females and 32 males.ResultsData showed that 517 (48.9%) nurses may have depression. Results from the structure equation modeling indicated that perception of social distancing mediates between individuals in units of care and depression, while unit and tenure of nursing work were negatively associated with depression.ConclusionThe study findings support that perceived social distancing due to COVID-19 pandemic from others toward nurses may have influential impact on elevated depression, especially for nurses worked in the acute critical care. Thus, emotional support should be emphasized, and avenues for stress relief should be provided as well as creating a supportive workplace environment is crucial to nurses and patient safety.